Pengaruh Strategi Pemilihan Tempat Belanja terhadap Pemenuhan Kebutuhan Keluarga - Jannah, Zulfah Azkiya; Rustomo, Rustomo; Imanudin, Kaffah (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The rise of online stores in Indonesia makes shopping easier for consumers with the various facilities provided, making it attractive for consumers to be lazy about visiting conventional stores. This change in shopping lifestyle is because traditional markets are visited more by people who need goods in large quantities or wholesale at low prices. Meanwhile, modern markets are a shopping option with a small number of goods rather than specific ones and more adequate comfort. The objectives of this research are (1) To find out where people choose shopping places, (2) To find out people fulfill their family needs, (3) To find out the influence of choosing shopping places in streamlining family needs. This research will be built with an experimental research design to determine the relationship between cause and effect of a situation using a descriptive quantitative approach with survey research methods. The population in this study were residents of Cawang RT 006 RW 02 Cawang, East Jakarta, with a total of 32 heads of families, where the entire population was also used as the research sample. The result of this research is that the Sig value for the influence of X on Y is equal to 0,000 > 0,05 and tcount value 4,692 > ttable 2,045, so it can be concluded that the choice of shopping place influences the family's needs. The family's needs are urgent and must be purchased immediately, so a physical store is needed as the solution. If you buy from an online shop, it takes time for delivery, so what you can buy are items that are not urgent to use. Shops/stalls influence family needs as a place to buy various family needs